Remoção de ferro em água por adsorção em batelada e leito fixo utilizando alga marinha Lithothamnium calcareum em diferentes tratamentos - Almeida, Antônio Ewerton da Silva (2018)
The development of economic activities associated with high yields and minimized environmental impactsis challenging, especially when related to water resources preservation. This study aimed to evaluate iron adsorption processes and to obtain transport parameters in columns filled with Lithothamniumcalcareum algae submitted to different treatments. Natural algae (without treatment), and algae submitted to thermal, chemical, and thermochemical treatments were used. The following characterizations were performed: scanning electron microscopy, X-ray diffraction, specific surface area, and Fourier transform infrared spectroscopy. In the kinetics tests, Fe2+ concentrations in the supernatant solution were determined at 2, 5, 10, 20, 60, 120, and 180 minutes of stirring on a shaker, rotating at 60 rpm. A total of 0.2 g of algae were added toErlemeyers containing 15 mL of iron sulfate solution at 5.0 mg L-1 Fe2+. The experimental data of the kinetic study were fitted to the following models: Elovich, pseudo-first order, pseudo-second order, Weber and Morris, and Sigmoidal. For the isothermstudy, Fe2+ solutions were used at the concentrations of 5, 10, 20, 50, 100, 250, and 500 mg L-1. The results were adjusted to the following isotherm models: Linear, Freundlich, Langmuir, Sips, Redlich-Peterson, Temkin, and Lorentz. In the miscible displacement test of the Fe2+ solution, an acrylic column filled with thermochemically treated algae was fixed on a constant charge permeate with two Mariotte flasks, one containing deionized water and the other containing 500 mg L-1 sulphate displacing solution. The column was fed in an upward flow. In this test, five hydraulic loads (2, 4, 6, 8, and 10 cm) and two adjustment models (Model A0 and A1) were evaluated. The transport parameters were analysed using Excel® and the Stanmod and Disp applications in order to compared to the values obtained by the Stanmod. For this, the average relative errors between the relative concentrations were calculated. The treatments promoted an increase in the surface area of the algae without compromising its chemical composition and crystalline structure. The chemical and thermochemical treatments increased Fe2+ adsorption rate, being best adjustmented for the sigmoidal, pseudo-first order, and the intraparticle diffusion models. The models of Lorentz and Sips best described the adsorption process, and the algae submitted to the thermochemical treatment caused higher Fe2+ removal. The A0 and A1 models described well the experimental results, indicating the predominance of dispersive flow. The values of the adjusted elution curves provided lower average relative errors when compared to Disp. The R values indicated high interaction between algae and Fe2+ regardless of the applied hydraulic load. The studied algae obtained satisfactory efficiency in the removal of high concentrations of iron in water.